PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN MEDIA KONKRET TERHADAP KOMPETENSI PENGETAHUAN IPA SISWA KELAS IV SD GUGUS DEWI SARTIKA DENPASAR TIMUR TAHUN PELAJARAN 2017/2018 - kadek Diah Sari (Universitas Pendidikan Ganesha, 2018)
The purpose of this study was to know the significant different in science knowledge between the group of students who were taught through Guided Inquiry Learning Model assissted by concrete media and the group of students who were taught through conventional learning model at grade IV students of SD Gugus Dewi Sartika Denpasar Timur in academic year 2017/2018. The population of this research was all fourth grade students of SD Gugus Dewi Sartika Denpasar Timur in academic year 2017/2018. The sampling was conducted by random sampling technique by randomizing class. The sample of this research was IV B of SD N 10 as experimental group and IV B of SD N 3 Kesiman as control group with the total number of experimental group was 40 students and the contol group was 41 students. The data collected was the data of the competency of science knowledge and analyzed by t-test. After being analyzed by t-test, obtained tcount = 2,372 at significance level 5% ( = 0,05) with dk = 79 and ttable (a = 0,05) = 2.000. Based on the test value tcount = 2.372 > ttable (a = 0,05) = 2.000. The results showed that experimental gained more score in compared to control group with mean of = 0,41> = 0,31, it can be concluded that there is an effect by implementing Guided Inquiry Learning Model toward science knowledge competence. Thus, there is a significant difference between the science knowledge of the group which were taught through Guided Inquiry Learning Model assissted by Concrete Media and the group of students who were taught through conventional learning in IV grade students of SD Gugus Dewi Sartika East Denpasar in academic year 2017/2018.